Identifying modifiable factors associated with COVID-19 vaccine hesitancy and acceptance among cancer patients in Jordan - AlMasri, Rama; Al Masri, Mahmoud; Darwish, Rula; Ammar, Khawla; Safi, Yasmin (Frontiers in Oncology, 2023)
Vaccines stand amongst the most effective medical interventions for the management of infectious diseases, and are pivotal tools for public health. The acceptance of vaccines is heavily influenced by perceptions of efficacy, safety and other modifiable factors. Purpose: This crosssectional study sought to identify and examine the modifiable factors that can help address COVID-19 vaccine hesitancy and acceptance among cancer patients. Methods: The study was conducted between February and April 2021 using an online survey questionnaire comprising of four domains. The survey was administered to cancer patients in Jordan. Results: Among the 1,029 cancer patients who completed the online questionnaire (response rate= 73%), 58% (n=597) expressed willingness (intent) to take the vaccine. Notably, 72.5% (n=433) of those intending to take the vaccine were currently undergoing treatment. Knowledge and awareness played a significant role, with 54.3% considering them essential for vaccine acceptance. Fear of infection significantly influenced vaccine acceptance (p<0.001), with 66.8% expressing concern about potential infections. Peer encouragement was also a crucial factor, as 82.4% regarded it as an important driver for influencing vaccine acceptance (p<0.001). Conclusion: Peer encouragement, awareness, and fear emerged as the primary modifiable factors associated with greater vaccine acceptance by patients with active malignancies. Study results suggest that providing personalized and tailored information about vaccinations, focusing on safety and potential interactions with cancer and its treatment, are potentially excellent strategies for improving vaccine acceptance among cancer patients.